Canada : Financial Sector Assessment Program-Technical Note-Insurance Sector: Regulation and Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This chapter on Financial Safety Net and Crisis Management for the Canada reviews the insurance sector's regulation and supervision. The paper highlights that Canada has a highly developed insurance market that is important to Canada's economy. Regulation and supervision of the insurance sector in Canada is conducted by the federal and provincial authorities. Insurers can be incorporated under the federal or provincial regime. At the federal level, the Office of the Superintendent of Financial Institutions (OSFI) is responsible for prudential regulation and supervision of federally regulated insurers. The provincial supervisors oversee prudential oversight of provincially regulated insurers and conduct oversight of all insurers operating in their jurisdictions. Federal-provincial cooperation and coordination should be further improved. Group-wide supervision needs improvement in legal foundation and consistency of application. With no legal powers over unregulated holding companies, both OSFI and Autorite des marches financiers rely on voluntary agreements with the companies to be able to obtain information and apply prudential requirements for the insurance groups.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet